PENGARUH PROMOSI INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN MILLENIAL DOMESTIK KE CURUG CIHERANG BOGOR - Erika Arifin; I Putu Sudana; Putu Agus Wikanatha Sagita (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
Social media is considered the most effective media in promoting both goods and services. One form of social media used for tourism promotion is Instagram which is a photo and video sharing application. Curug Ciherang uses Instagram as a promotional medium that can bring tourists from various regions in search of information about Curug Ciherang. The purpose of this study was to determine the effect of Instagram social media promotion on the visiting decision of domestic tourists millennial to Curug Ciherang. This study used mixed methods techniques which include qualitative and quantitative descriptive analysis. The sampling technique was taken by purposive sampling with a total of 100 respondents of domestic millennial tourists who had visited Curug Ciherang. Data collection techniques in this study by observation, interviews, questionnaires, literature study, and documentation. This research uses validity test, reliability test, simple linear regression analysis test, classical assumption test, t test, and determination test with the help of SPSS version 24 software for Windows. The results of the research based on the t-test showed that the significance value was 0.000 <0.05 and the t-count value was 11.868> t-table 1.985. So that promotion on social media Instagram has a positive effect on the visiting decision of domestic millennial tourists to Curug Ciherang. The magnitude of the coefficient of determination is equal to 59%.